Tula hantavirus infection in immunocompromised host, Czech Republic - Zelená, Hana; Mrázek, Jakub; Kuhn, Tomáš (Emerging infectious diseases, 2013)
We report molecular evidence of Tula hantavirus as an etiologic agent of pulmonary-renal syndrome in an immunocompromised patient. Acute hantavirus infection was confirmed by using serologic and molecular methods. Sequencing revealed Tula virus genome RNA in the patient's blood. This case shows that Tula virus can cause serious disease in humans.
Keywords: RNA, Viral; viruses; hemorrhagic fever with renal syndrome; RNA virová; Male; Tula virus; protilátky virové; Lung Diseases; Orthohantavirus; Genome, Viral; fylogeneze; Adolescent; Hemorrhage; Česká republika; Phylogeny; molekulární sekvence - údaje; Glomerulonephritis; mužské pohlaví; immunocompromised host; mladiství; Immunocompromised Host; krvácení; Czech Republic; Hantavirus Infections; lidé; Hantavirus; hantavirové infekce; imunokompromitovaný pacient; Humans; glomerulonefritida; hantavirus; plicní nemoci; Antibodies, Viral; genom virový; Molecular Sequence Data; hantavirus pulmonary syndrome